Fatimskie przemówienia papieży - Warzeszak, Józef (Warszawskie Studia Teologiczne, 2017)
The analyses of papal speeches related to Fatima apparitions allow to learn about the personal engagement of each of the Popes in accepting the Fatima messa-ge and its implementation by the acts of entrustment and devoting the Church and the world to the Immaculate Heart of Mary in order to save it from the dangers. Knowing the papal texts allows to learn about the authentic, profound theology of those apparitions the trinitarian, christological, ecclesial, spiritual and existential context. The Popes indicate close relationship between Mary and Christ and God’s salvation plan. They justify the need for conversion, prayer, especially with the Rosary, penance, compensation, as these are the means which allow for the healing of the world, saving its future and salvation of souls. God’s Mother of Fatima brings hope to the world, strengthens the faith and reveals God’s merciful love.